Analysis of aroma components in different longan fruit wines based on HS-SPME-GC-MS - XU Jia, LI Jiajun, ZHU Wenhai, PENG Xuan, LIANG Libao, FU Li (Zhongguo niangzao)
In this study, longan fruit wine was prepared by using longan as raw material and three Saccharomyces cerevisiae (LABA, CRI, L-EL) as fermentation strains. The aroma components of longan fruit wine were analyzed by headspace solid phase microextraction gas chromatography mass spectrometry (HS-SPME-GC-MS) method, and the contribution of each aroma component to the overall flavor of longan fruit wine was evaluated by combining relative odor activity value (ROAV) to identify key aroma components. The results showed that 58 kinds of volatile flavor compounds were detected in longan fruit wine brewed by 3 kinds of S. cerevisiae, including 19 esters, 8 alcohols, 7 aldehydes, 2 alkenes, 4 acids, 3 ethers, 5 phenols, 6 aldehydes and ketones and 4 furans. There were 43 kinds of volatile flavor substances in fruit wine fermented by CRI yeast, the highest ester content (1.54 g/L), and 7 key aroma components (ROAV≥1), namely ethyl butyrate, ethyl caproate, ethyl enanthate, ethyl caprylate, methyl salicylate, diethyl succinate and ethyl phenylacetate. Therefore, yeast CRI is suitable for brewing longan fruit wine.